One-Pot Synthesis of Hydroxylated Alkaloids from Sugars via a Pictet–Spengler-Type Reaction - Likai Zhou; Na Ma; Jilai Wu; Weilin Yang; Lijing Feng; Song Xie; Lili Wang; Hua Chen (Molecules, 2024)
An efficient and convenient strategy has been successfully developed for the preparation of novel hydroxylated alkaloid derivatives (also called fused multicyclic iminosugars) from p-toluenesulfonylated sugars through a Pictet–Spengler-type mechanism. This method is highly stereoselective, does not require metal catalysts, and capable of conducting gram level reactions (with a 53% yield). Some of such iminosugars had an intermediate antiproliferative effect on HCT116 tumor cells.